2018
DOI: 10.12681/jhvms.18015
|View full text |Cite
|
Sign up to set email alerts
|

Prion protein gene polymorphisms in classical scrapie-affected flocks of sheep in Central Macedonia

Abstract: Research articlesheep, 340 were of Chios breed, 633 Chios crossbred and 483 crossbred. The examined sheep showed high genotype variability, as a total of 7 haplotypes and 23 different genotypes were found. The predominant allele and the predominant genotype were ARQ and ARQ/ARQ respectively, in all breeds studied, followed by the ARR allele and the ARR/ ARQ genotype. The TRQ allele was frequent in Chios and Chios crossbred, while the VRQ allele was rare for all the breeds. Interestingly, 3 genotypes (ARH/TRQ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Our findings showed that the ARQ/ARQ genotype was found predominant (0.40) for Turkish Awassi sheep in this study (Table 3). This observation is coherent with the previous study (0.53) for Awassi sheep in Türkiye [9] as well as reports on other breeds in different countries [21,25,28,32,35,36]. In contrast to Turkish Awassi sheep, the ARQ/ARH genotype was predominant in Palestinian and Saudi Arabian Awassi sheep, with frequencies of 0.36 and 0.48, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings showed that the ARQ/ARQ genotype was found predominant (0.40) for Turkish Awassi sheep in this study (Table 3). This observation is coherent with the previous study (0.53) for Awassi sheep in Türkiye [9] as well as reports on other breeds in different countries [21,25,28,32,35,36]. In contrast to Turkish Awassi sheep, the ARQ/ARH genotype was predominant in Palestinian and Saudi Arabian Awassi sheep, with frequencies of 0.36 and 0.48, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, scrapie breeding programs should be implemented in these regions to increase the incidence of the ARR allele. Most studies conducted in sheep populations across the world have demonstrated that the predominant allele is ARQ [8,9,27,[29][30][31][32][33][34]. The ARQ allele is thus regarded as the ovine wild-type allele.…”
Section: Discussionmentioning
confidence: 99%